2018
DOI: 10.1111/cpr.12522
|View full text |Cite
|
Sign up to set email alerts
|

AP2a enhanced the osteogenic differentiation of mesenchymal stem cells by inhibiting the formation of YAP/RUNX2 complex and BARX1 transcription

Abstract: Objectives: Bone regeneration by bone tissue engineering is a therapeutic option for bone defects. Improving the osteogenic differentiation of mesenchymal stem cells (MSCs) is essential for successful bone regeneration. We previously showed that AP2a enhances the osteogenic differentiation in MSCs. The present study investigated the mechanism of how AP2a regulates the direct differentiation. Materials and methods:Co-immunoprecipitation and ChIP assays were carried out to investigate the underlying mechanism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…The findings of Lin et al (2019) may shed some light on the ambiguous role of YAP in regulating osteogenesis. They found that YAP binds to and inhibits the upstream pro-osteogenic transcription factor RUNX2 in human bone marrow and dental-derived MSCs, and that this inhibition is released by competitive binding of AP2a (activator protein 2a) to YAP ( Lin et al, 2019 ). Thus, YAP binding and inhibition of RUNX2 may serve as a negative feedback mechanism to YAP activation of RUNX transcription through TEAD, and AP2a may provide a release from this negative feedback mechanism.…”
Section: Modulation Of Stem/progenitor Cell Lineage Fate By Yap/tazmentioning
confidence: 96%
See 4 more Smart Citations
“…The findings of Lin et al (2019) may shed some light on the ambiguous role of YAP in regulating osteogenesis. They found that YAP binds to and inhibits the upstream pro-osteogenic transcription factor RUNX2 in human bone marrow and dental-derived MSCs, and that this inhibition is released by competitive binding of AP2a (activator protein 2a) to YAP ( Lin et al, 2019 ). Thus, YAP binding and inhibition of RUNX2 may serve as a negative feedback mechanism to YAP activation of RUNX transcription through TEAD, and AP2a may provide a release from this negative feedback mechanism.…”
Section: Modulation Of Stem/progenitor Cell Lineage Fate By Yap/tazmentioning
confidence: 96%
“…As described earlier, an intracellular protein that binds directly with YAP is AP2a, with formation of the YAP-AP2a protein complex releasing YAP binding and inhibition of RUNX2 activity (Lin et al, 2019). Additionally, the YAP-AP2a protein complex blocks transcription of BARX1, which inhibits osteogenesis (Lin et al, 2019). Snail and Slug are zinc-finger transcription factors that interact directly with both YAP and TAZ, thereby promoting osteogenesis via activation of RUNX2 transcription (Panciera et al, 2016;Tang et al, 2016).…”
Section: Role Of Yap/taz In Stem Cell Self-renewal and Maintenance Ofmentioning
confidence: 97%
See 3 more Smart Citations